The Development Of Strength Ecercise Method For Children Age 9-14 Years In Volleyball - Eka Supriatna; Rahmat Putra Perdana (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2021)
Based on observations made in volleyball clubs throughout Pontianak, there is no Instructional VCD that broadcast strength training For children 10 to 14 years of age, it is necessary to develop a VCD strength training instructional method. The aim of this study was to develop instructional VCD volleyball strength training methods for children aged 10 to 14 years. This development uses an R&B development model with the ADDIE development model. Meanwhile, the data analysis technique, namely the percentage, was adopted from Sudjana (2016). The results of the development of the VCD instructional strength training method met the criteria valid enough for media experts to obtain 90.97% of the Very Eligible category, the material experts obtained 85% of the Very Eligible criteria, for the volleyball coach's assessment obtained 90% of the Very Eligible category, and the assessment for the trial group stage II obtained 87.77%. The conclusion of this study is that the development of instructional video-based strength training methods is very suitable as a medium for strength training in children aged 10 to 14 years.